(untitled) (Research, Society and Development, 2025)
This study aims to compare in-hospital mortality, costs, and length of stay between traditional cardiovascular surgery and interventional cardiology in SUS (2009–2023), evaluate temporal trends in technological substitution, and quantify long-term effects using risk-adjusted models. An ecological design analyzed aggregated data from 2,303,648 procedures. ARIMA models and negative binomial regression adjusted temporal trends and mortality risk. Results revealed accelerated technological substitution (-1.27% annual decline in surgeries; p < 0.001), with initial mortality advantage for interventional procedures (RR = 0.43; 95% CI: 0.11–0.76). However, synthetic projections showed benefit inversion by 2023 (+72.38 excess deaths), linked to an inverse learning curve for interventions (+0.83% mortality per 1% volume increase; p < 0.001). Cost savings (R5,524/case) and shorter hospitalization (-5.07 days) coexisted with rising complexity in surgical cohorts, increasing baseline mortality risk by 0.59% annually (p < 0.001). The study concludes that technological substitution in SUS achieved economic efficiency but requires parallel investments in training and risk stratification for clinical sustainability.